ANALISIS AKUNTABILITAS SISTEM ARSIP PADA KOMISI PEMILIHAN UMUM PROVINSI BALI DALAM PERSPEKTIF GOOD GOVERNANCE - Djarut, Adelia; Ni Wayan Widhiasthini; Ni Ketut Arniti; Ni Putu Bayu Widhi Antari (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the accountability of the archiving system at the Bali Provincial General Election Commission (KPU) from a good governance perspective, focusing on four key accountability dimensions: legal and honesty accountability, process accountability, program accountability, and policy accountability. The research was conducted at the Bali Provincial KPU Office using a descriptive qualitative approach. Data were collected through in-depth interviews with the Chairperson of KPU Bali, the Head of the Finance, General Affairs and Logistics Division, the Head of the General Affairs and Logistics Subdivision, SRIKANDI system operators, and media representatives. The researcher also carried out direct observations of archival practices and analyzed supporting documents, including Law No. 43 of 2009, PKPU Regulation No. 17 of 2023, and the KPU’s archival retention schedule. Data were processed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings show that KPU Bali has implemented an archival system that complies with established legal frameworks and formal procedures, covering document creation, storage, digitalization, and disposition, with destruction requiring approval from ANRI. The use of the SRIKANDI and SINAR applications strengthens process accountability by modernizing archival management and improving administrative efficiency. From a program perspective, the archiving system supports the overall performance of election administration and institutional duties. Policy accountability is reflected in public information transparency through the Public Information and Documentation Officer (PPID) and consistent communication with the media. The archival system at the Bali Provincial KPU operates in an accountable and transparent manner in line with good governance principles, although further improvements in facilities, human resources, and digital optimization are needed to ensure sustainable and effective public information services.